Relações de proximidade e espaços televisivos em telejornais locais e regionais de Minas Gerias: o caso dos Praça 1 - José Tarcísio da Silva Oliveira Filho (2019)
This thesis proposes to observe the local and regional TV journalism in Brazil, focusing on the concept of proximity in five regional newcasts, known as Praça 1 – produced by TV Globo's affiliated (commercial TV) and organized in a network. Through the discussion about local journalism, it reflects about problematic approaches, such as the exclusively of the geographical delimitation and the use of the community term. Instead deal with proximity as News Value, the discussion proposes its approach as a relation. Thus, five initial relations were systematized to observe the proximity in regional TV news: TV casts-audience; TV casts-territory; news-journalists; format-audience; and subject-audience. These relationships are not mutually exclusive and can coexist with one another. In order to observe these relationships, two analyzes were develop. The preliminary, in which 352 videos were collected in four Minas Gerais “Praça 1” websites: MG1 Triângulo de Minas (TV Integração - Uberlândia / Uberaba), MG1 Vales de Minas (InterTV - Governador Valadares), MG1 Grande Minas (InterTV - Montes Claros) and EPTV Primeira Edição Sul de Minas (EPTV - Varginha). The material was collected in the years 2018 and 2019 totaling twelve days of exhibition and also serve as the basis for the elaboration of four operators for a second analysis, this time with the MGTV Primeira Edição of Zona da Mata and Campo das Vertentes (TV Integração/Juiz de Fora). In the second part, we opted for a full view of six editions collected in June 2019. On the one hand, The analyzes demonstrated that the identity and cultural aspects that surround proximity are subordinated to generalist and normative policies of journalistic processes on a (national) scale that sometimes do not allow professional formats and practices to be genuinely constituted at the local and regional levels. On the other hand, it shows that the local sense cannot be taken only by geographic coverage. It has been identified that the subjects (such as service), scenic space and performances developed by regional news broadcasts also contribute to build a sense of place in the television dimensions.